Year Work Tradition (Merdang Mardeng) as Traditional Communication in the Karo Tribe Community in Dokan Cultural Village - Camelia Asmawiyah; Abdul Rasyid (IHSA Institute, 2022)
Tanah Karo is an area occupied by the majority of the people of Karo ethnicity. In this tribe there are many lessons, the Merdang Mardem tradition teaches the author that multicultural cultural communities can coexist. Therefore, culture is a bridge that can unite people in differences. The tradition of Merdang Mardem in ancient times was used by the community to celebrate the overflowing harvest. This is then inherited and continues to be done by the community regardless of any belief or religion.